Drinking extra water or other non-caloric beverages for promoting weight loss or preventing weight gain - Burls, A; Price, A; Cabello, J; Roberts, N (John Wiley and Sons, Ltd, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effects of drinking extra water or other non-caloric beverages for promoting weight loss or preventing weight gain.